INTERAKSI SOSIAL PERTUNJUKAN RONGGENG NAK MUDO PINANG SARUMPUN DI MASYARAKAT NAGARI SIMPANG MUDIAK KABUPATEN PASAMAN - Niken Rahayu Jovia Putri; A.A.I.A, Citrawati; Nurmalena Nurmalena (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This writing aims to determine social interaction in performance of Ronggeng Nak Mudo Pinang Sarumpun at Nagari Simpang Mudiak community, Pasaman Regency. This Ronggeng performance is shown between the Ronggeng performers and the audience or the audience and the dancers, who interact through communication by attracting the attention of the audience through poem with the rhymes that are sung. This study used qualitative methods with data collection techniques of observation, interviews, and documentation, then analyzed using Sudariyanto social interaction theory and Alo Liliweri communication theory. The results showed that in the Ronggeng Nak Mudo Pinang Sarumpun performance, there was social interaction between the people of Simpang Mudiak and the Ronggeng performers, and the establishment of friendly intrapersonal communication through poem rhymes as message deliverer and message recipients by dancers and audiens in the Ronggeng Nak Mudo Pinang Sarumpun performance.